The Government Communication Strategy through Social Media to Increase Public Awareness - Jamalullail Jamalullail; Fidan Safira; Hamdi Hamdi (Nyimak: Journal of Communication, 2023)
Public communication for the government is crucial to establish interaction and build public trust. This study aims to identify the goals and forms of government communication strategies using social media. This research uses the SLNA (Systematic Literature Network Analysis) method with limitations on emerald and science direct data sources published in the 2018-2022 range. Network Analysis is used to map keywords from selected articles to find theme patterns. The findings of this study indicate that the government uses social media not always to show reputation or transparency, but rather to socialize to increase awareness and interaction. However, the impact of using social media shows more community participation than awareness.